Analisis Penetapan Harga Jual Dengan Metode Pendekatan Biaya (Cost Oriented Approach) Terhadap Produksi Kerupuk Sambal Canga Kota Sibolga - Lubis, Amyra Zhahra; Maidalena, Maidalena; Harianto, Budi (Jambura Economic Education Journal, 2025)
The purpose of this research is to determine the analysis of selling price determination using the Cost Approach Method for the production of canga chili sauce crackers in the city of Sibolga, and to find out what the Islamic economic concept of price determination is. This research method uses a case study research design using qualitative descriptive techniques. Data collection techniques using interviews with the owner of the canga chili cracker company in Sibolga City. The data source is based on primary data, namely direct observation and interviews with the canga chili cracker business in Sibolga City. The results of the research show that the cost-oriented approach used to determine the selling price of Sibolga City sambal canga crackers produces a price that is significantly different from that set by the business. When a business uses the Cost Oriented Approach method, it bases the selling price of the product on the selling price of its competitors and with this method includes all capital calculations.